Exploring Faculty Members’ Experiences with Virtual Classroom Platforms and Their Perceived Usability during the COVID-19 - Yunus Alkış; Zafer Kadırhan; Mustafa Şat (e-Kafkas Eğitim Araştırmaları Dergisi)
This two-phase mixed-method study examined faculty experiences with Virtual Communication Platforms (VCPs) and their usability in distance education during the COVID-19 epidemic. A stratified random sample of 913 faculty members from 167 universities was selected to participate in an online questionnaire that included the System Usability Scale, demographic information, and open-ended questions. Twenty-five of the faculty members who had completed the online questionnaire were then interviewed in semi-structured interviews. The quantitative analysis results indicate that Zoom was the most favored platform, obtaining a ‘Good’ usability score together with Google Meet and Adobe Connect. In contrast, Perculus and Microsoft Teams were evaluated as having ‘Poor’ usability. Results also revealed the significant effect of gender on Perculus, distance education experience on Zoom, and age and academic status on Zoom and Google Meet usability perceptions. Furthermore, the qualitative analysis results revealed usability challenges (e.g., technical challenges, functionality issues, usability concerns), positive aspects (e.g., usability and effectiveness, support and issue resolution, performance and accessibility), and suggestions for improvement (e.g., instruction and support, exploration and optimization, format and assessment enhancement). The study offers valuable insights for institutions to make informed decisions about adopting VCP, investing in targeted training programs, and ultimately fostering a more effective and inclusive distance education environment.